Ethno-sectarian division and the predicaments of national integration in plural societies: a study of Nigeria and Iraq - Qader, Mohammed Mustafa; Masum, Ahmad; Abdul Rahman, Rohana; Usman, Abbo (Center for Sustainabality Research & Consultancy, 2016)
Objective: The purpose of this paper is to examine the problem of sectarianism in Nigeria and Iraq, as both countries provide typical examples of ethno-sectarian divided societies characterized by huge contrasts in social norms and religious values among the citizens. Methodology: Adopting content analysis, the current paper argues that ethno-sectarianism negatively affects political process in both countries which invariably undermines their effort toward national integration.The paper seeks to answer the following question: will restructuring the Nigerian and Iraqi federal relations contribute to resolving sectarian tensions? First, the paper examines the sources of sectarianism in both countries.The paper therefore examines how ethno-sectarianism shaped and molds the polity of both countries, where ethnic and religious values play major role in determining citizen’s reaction to political phenomenon Results: Coordination mechanisms such as framework legislation and dispute resolution committees are also necessary to ensure that the transition to viable federalism occurs with minimal encumbrance.To respect the complex and diverse identities of nations, safeguards need to be established to protect the rights of sub-federal nations.For example, the political future of Iraq and Nigeria is not a return to failed approaches of division, but rather the construction of a viable modern federal state that promotes unity, political compromise, and consensus building.Implication: This paper therefore posits that there is a need for deep mental changes and social adjustment among the citizens of both countries where attributes such as tolerance, dignity of human persons and above all patriotism must be re-defined and this requires collaboration between political leaders, community leaders and religious bodies as the problem is societal bound.